Analisis Pengaruh Penggunaan Bahasa Indonesia dalam Komunikasi Bisnis terhadap Lingkungan Kerja: Studi Kasus Pada Gen-Z - Manalu, Tressia Anjelina; Febriana, Ika; Betsyeba, Jelitha; Sinaga, Sri Rahayu; Pandiangan, Gita Tri Novel; Samosir, Ruth Valentina (Universitas Negeri Padang, 2024)
The purpose of this study is to examine how the use of Bahasa Indonesia influences business communication in the work environment, with a particular focus on Generation Z. In the context of rapid globalization, the ability to communicate effectively is key to success in the business world. Generation Z, as digital natives, exhibit unique communication characteristics and often use informal language that can potentially hinder professionalism in the workplace. Using a case study of a Generation Z employee at a fund management company in London, this research proves that the use of casual language can damage an individual's credibility and is not in line with company expectations. The results show that proper use of Bahasa Indonesia can improve the quality of interactions, strengthen relationships between teams, and increase work productivity. Therefore, organizations need to understand and accommodate the communication characteristics of Generation Z in order to create an inclusive and productive work environment.